2019
DOI: 10.1039/c9ay01770d
|View full text |Cite
|
Sign up to set email alerts
|

Salting-out-assisted liquid–liquid extraction of 5-hydroxymethylfurfural from honey and the determination of 5-hydroxymethylfurfural by high-performance liquid chromatography

Abstract: A simple, rapid, and effective sample preparation method was developed for the recovery of 5-hydroxymethylfurfural from honey samples with negligible co-extracted sugars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The former, MgSO 4 , has been demonstrated to be an efficient phase-separation agent as the high extraction yield for relatively high-polarity compounds [36]. The latter, NaCl, was used to reduce the co-extracted protein and sugar contents from the matrix [37,38].…”
Section: Salting-out Assisted Liquid-liquid Extractionmentioning
confidence: 99%
“…The former, MgSO 4 , has been demonstrated to be an efficient phase-separation agent as the high extraction yield for relatively high-polarity compounds [36]. The latter, NaCl, was used to reduce the co-extracted protein and sugar contents from the matrix [37,38].…”
Section: Salting-out Assisted Liquid-liquid Extractionmentioning
confidence: 99%
“…Results obtained from the real samples indicated that HMF in the fresh honey was at very low level, whereas in commercial samples, heat treatment and long-term storage could lead to significant increases in HMF concentration. More importantly, since the phase separation of HLLE dramatically decreases the residual content of sugars in the extractive [ 17 ], this field sample preparation may reduce the impact of the sample transport process on the promotion of HMF production. In addition, four phenolic compounds were also detected in the samples, including protocatechuic acid, caffeic acid, and kaempferol in three commercial samples and 3,4-dimethoxycinnamic acid in four raw samples.…”
Section: Resultsmentioning
confidence: 99%
“…After phase separation, multiple analytes with a wide range of polarities can be rapidly and efficiently extracted into the separated organic phase [ 12 , 13 , 14 , 15 ]. Moreover, the phase separation also makes high-polarity matrix compounds e.g., proteins [ 16 ] and sugars [ 17 ] mostly stay at the aqueous phase, which significantly reduces the interference. In addition, the obtained extractive solution is compatible with dispersive solid-phase extraction (d-SPE) [ 18 , 19 ], disposable pipette extraction (DPX) [ 20 ], matrix solid-phase dispersion [ 21 ], and dispersive liquid–liquid micro-extraction (DLLME) [ 22 , 23 , 24 , 25 ] for further clean-up or enrichment.…”
Section: Introductionmentioning
confidence: 99%
“…Various modifications of the HPLC method have been reported, including sample preparations using liquid-liquid extractions (Chen et al, 2019). In addition, methods using high-performance thin layer chromatography, gas chromatography, and micellar electrokinetic capillary chromatography have been developed for analysing HMF in honey (cited in Chen et al, 2019), but these methods are not commonly used. For a complete list of all methods for the determination of HMF in food see Morales (2009).…”
Section: Analytical Methods For Detection and Quantification Of Hmfmentioning
confidence: 99%